Agroecological aspects of microbial preparations application on the winter triticale crops - Писаренко, П. В.; Москалець, В. В.; Москалець, Т. З.; Москалець, В. І. (Scientific Progress & Innovations, 2012)
The sensitivity of the winter triticale genotypes to the microbial preparations activity has been studied. It has been noted that each variety of winter triticale differently sensitive to the activity of microbial preparations. Plant varieties AD 256, Slavetne, Jaguar, Vivate Nosivsky are more sensitive according to the productive indices in case of using both nitrogen-fixing and fosfatmobilizing microorganisms, plant varieties DAU 5 and Yaguar – using diazobakterin, variety Augusto – albobakterin.